Facial biocosmetics based on natural dyes from Amazon wood residues - NICARETTA, Brenna Couto (Universidade Federal do Oeste do Pará, 2024)
The occurrence of several flavonoids with antioxidant and antiinflammatory potential properties in wood may have a viable application in the biocosmetic industry. This paper studies the technical viability of redirecting wood residues of the main commercialized Amazonian species, Dipteryx odorata (cumaru), Manilkara huberi (ironwood), Hymenaea courbaril (Brazilian cherry) and Handroanthus serratifolius (yellow ipe), to obtain natural dyes for facial biocosmetics development. For each dye sample, phytochemical profile of phenolic compounds and the total flavonoids content expressed in rutin and quercetin (ug mL–1) was determined. Wood residues extract yield was 6.5% for cumaru, 8.1% for ironwood, 16.3% for Brazilian cherry and 8.8% for yellow ipe. The physical-chemical properties were compliant with the official compendia. TLC-analysis revealed the presence of flavonoids (quercetin) and hydrolyzable tannins (gallic acid). Concentration of total flavonoids content expressed in rutin and quercetin varied between 0.106 to 7.5 and 0.1 to 3.12ug.mL–1, respectively, for all species. Facial biocosmetic formulations with organoleptic properties (appearance, color and odor) suitable for facial use could be obtained from ironwood, Brazilian cherry and yellow ipe dyes. Therefore, Amazon species wood residues reuse is an innovative and sustainable technological strategy to add value to bioproducts of Amazon biodiversity, contributing to the region’s socio-economic development.